Amplitude differences in high-frequency fMRI signals between eyes open and eyes closed resting states - Yuan, Bin-Ke; Wang, Jue; Zang, Yu-Feng; Liu, Dong-Qiang (Frontiers in Human Neuroscience, 2014)
Recent studies employing rapid sampling techniques have demonstrated that the resting state fMRI (rs-fMRI) signal exhibits synchronized activities at frequencies much higher than the conventional frequency range (< 0.1 Hz). However, little work has investigated the changes in the high-frequency fluctuations between different resting states. Here, we acquired rs-fMRI data at a high sampling rate (TR = 400 ms) from subjects with both eyes open (EO) and eyes closed (EC), and compared the amplitude of fluctuation (AF) between EO and EC for both the low- and high-frequency components. In addition to robust AF differences in the conventional low frequency band (< 0.1 Hz) in visual cortex, primary auditory cortex and primary sensorimotor cortex, we also detected high-frequency (primarily in 0.1-0.35 Hz) differences. The high-frequency results without covariates regression exhibited noisy patterns. For the data with nuisance covariates regression, we found a significant and reproducible reduction in high-frequency AF between EO and EC in the bilateral primary sensorimotor cortex and the supplementary motor area, and an increase in high-frequency AF in the left middle occipital gyrus. Furthermore, we investigated the effect of sampling rate by down-sampling the data to effective TR = 2 s. Briefly, by using the rapid sampling rate, we were able to detect more regions with significant differences while identifying fewer artifactual differences in the high-frequency bands as compared to the down-sampled dataset. We concluded that 1) high-frequency fluctuations of rs-fMRI signals can be modulated by different resting states and thus may be of physiological importance, and 2) the regression of covariates and the use of fast sampling rates are superior for revealing high-frequency differences in rs-fMRI signals.